Effect of Nitrogen Fertilizer and Clipping Times on Forage Quality of Two Fenugreek (Trigonellafoenum-graecum) Varieties under Rainfed Condition of Sulaimani Region - Muhammed, Sanarya Rafiq (Sulaimani Journal for Pure and Applied Sciences, 2018)
A field experiment was laid out at College of Agricultural Sciences University of Sulaimani, during the winter season of 2014 – 2015 to study the effect of nitrogen fertilizer and clipping times on forage quality of two fenugreeks (Trigonellafoenum-graecum L.) varieties under rainfed condition using split-split plots based on randomized complete block design (RCBD) with 3 replications. Two varieties of Fenugreek (Mithe and EP 101) were allotted in the main plots and two levels of nitrogen fertilizer (0 and 40 kg/ha) in subplots and two clipping times as sub-sub-plots were investigated. The results indicated to significant effect of varieties on some quality traits (Protein, Digestible, protein and NDF) % only, EP101 variety recorded the highest percent of Protein and NDF (27.54 and 26.97) % respectively,while the highest Digestible Protein trait, the maximum percent was 83.42% exhibited by Mithe variety, while minimum value (83.04%) was obtained by EP101 variety. The nitrogen fertilizer affected significantly on (Fiber, ADF, NDF, ADL, K P) % and (Ca, Mg) % only. The highest values of them were (4.619, 14.56, 27.47, 3.140, 4.294 , 0.438) % and (0.272 and 0.210)% which were recorded from treatments N40 and N0 respectively, .The effect of clipping times on all forage quality traits was significant except (Fat, Ash, Ca and P)% which were not significant, first clipping time exhibited maximum percent of (Protein, DP, Fiber and Mg) which were (27.86%, 85.02%, 4.118%, and 0.213%) respectively, but the traits (ADF%, NDF%, Lignin%, ADL% and K%), recorded the highest values (16.89%, 28.12%, 1.663% 3.752% and 4.249%) respectively at second clipping time. The interaction among verities, nitrogen and clipping time affected only on protein, fat and Mg%.
Keywords: Fenugreek; nitrogen fertilizer clipping times varieties forage quality